Cosmic Web Research: Where are the Missing Dwarf Galaxies and the Inter-Galactic Hi Clouds. Issue Volume 14:Issue S344(2019) (August 2018) - Carignan, Claude
Abstract: We know that the observed H i (and H2 ) content cannot explain the SFR observed in galaxies. The only way galaxies can sustain that SFR is by accreting HI-rich dwarf galaxies or Inter-Galactic HI clouds. However, no observation to detect those accretion events has been conclusive so far. Instruments having the necessary sensitivity (e.g. GBT) lack the necessary spatial resolution and those with the proper resolution (e.g. VLA) lack the sensitivity. I will show that both are necessary to detect those illusive Hi clouds. The SKA precursor MeerKAT is starting its operation as we speak and will start the Large Survey Programs at the end of 2018. FAST has started its observations in drift scan mode with CRAFTS (Commensal Radio Astronomy Fast Survey). In the near future (2019-20), the best combination to study low column density H i will be to combine the sensitivity of FAST with the spatial resolution of MeerKAT.